Abacavir dosing in neonates from birth to 3 months of life: a population pharmacokinetic modelling and simulation study. Issue 1 (January 2022) - Bekker, Adrie; Capparelli, Edmund V; Violari, Avy; Cotton, Mark F; Cababasay, Mae; Wang, Jiajia; Mathiba, Ruth; Wiesner, Lubbe; Wiznia, Andrew; Samson, Pearl; Browning, Renee; Moye, Jack; et al.
Summary: Background: No evidence-based optimal dosing guidance is available for abacavir liquid formulation use from birth. We used abacavir pharmacokinetic data from neonates and infants to determine an exact abacavir dosing strategy (mg/kg) for infants aged 0–3 months and to propose dosing by WHO weight band for neonates. Methods: Abacavir pharmacokinetic and safety data were pooled from three completed studies (1997–2020): PACTG 321 (USA), the Tygerberg Cohort (South Africa), and IMPAACT P1106 (South Africa). PACTG 321 and the Tygerberg Cohort were performed in neonates exposed to HIV receiving a single dose of abacavir. IMPAACT P1106 included predominantly low birthweight (<2500 g) infants on antiretroviral therapy enrolled when they were younger than 3 months. We developed a population pharmacokinetic model and performed simulations to achieve abacavir exposures (area under the curve for 0–12 h) within the target range of 3·2–25·2 μg·h/mL, previously reported in older children. Findings: 45 infants contributed 308 abacavir concentrations; 21 neonates were younger than 15 days. At first pharmacokinetic assessment, median postnatal age for PACTG 321 was 1 day and median bodyweight was 3·1 kg; for the Tygerberg Cohort it was 10 days and 3·3 kg; and for IMPAACT P1106 it was 73 days and 3·8 kg. Our model predicted a slow abacavir clearance of 2·51 mL/min per kg at birth, which doubled by 4 weeks of age. Therapeutic targets were achieved with exact abacavir doses of 2·0 mg/kg twice daily from 0 weeks to 4 weeks and 4·0 mg/kg twice daily from 4 weeks to 12 weeks. A fixed weight-band dosing strategy of 8 mg (for 2–3 kg), 10 mg (3–4 kg), and 12 mg (4–5 kg) abacavir twice daily achieved target exposures throughout the first 4 weeks of life without the need for dose adjustment due to age or bodyweight changes. No adverse events of grade 3 or higher were related to abacavir. Interpretation: Integration of these dosing strategies into national and international guidelines for the abacavir liquid formulation will expand antiretroviral options from birth and simplify the clinical management of neonates with HIV. Funding: National Institute of Allergy and Infectious Diseases, Eunice Kennedy Shriver National Institute of Child Health and Human Development, National Institute of Mental Health, and the Collaborative Initiative for Paediatric HIV Education and Research Programme.